Advances and optimization strategies in bacteriophage therapy for treating inflammatory bowel disease - Li, Yang; Li, Xiao-meng; Duan, Hao-yu; Yang, Kai-di; Ye, Jun-feng (Frontiers in Immunology, 2024)
In the advancement of Inflammatory Bowel Disease (IBD) treatment, existing therapeutic methods exhibit limitations; they do not offer a complete cure for IBD and can trigger adverse side effects. Consequently, the exploration of novel therapies and multifaceted treatment strategies provides patients with a broader range of options. Within the framework of IBD, gut microbiota plays a pivotal role in disease onset through diverse mechanisms. Bacteriophages, as natural microbial regulators, demonstrate remarkable specificity by accurately identifying and eliminating specific pathogens, thus holding therapeutic promise. Although clinical trials have affirmed the safety of phage therapy, its efficacy is prone to external influences during storage and transport, which may affect its infectivity and regulatory roles within the microbiota. Improving the stability and precise dosage control of bacteriophages-ensuring robustness in storage and transport, consistent dosing, and targeted delivery to infection sitesis crucial. This review thoroughly explores the latest developments in IBD treatment and its inherent challenges, focusing on the interaction between the microbiota and bacteriophages. It highlights bacteriophages' potential as microbiome modulators in IBD treatment, offering detailed insights into research on bacteriophage encapsulation and targeted delivery mechanisms. Particular attention is paid to the functionality of various carrier systems, especially regarding their protective properties and ability for colon-specific delivery. This review aims to provide a theoretical foundation for using bacteriophages as microbiome modulators in IBD treatment, paving the way for enhanced regulation of the intestinal microbiota.